KOMPLEKSITAS PEMENUHAN HAK PENYANDANG DISABILITAS YANG BERHADAPAN DENGAN HUKUM DI PENGADILAN TINGGI TANJUNG KARANG - Maghfira Nur Khaliza Fauzi (Balitbangda Provinsi Lampung, 2022)
Basically, people with disabilities need to get protection for those who are in conflict with the law in court, especially the Tanjung Karang High Court. In this case, it is necessary to take a deeper look at legal developments in terms of current legislation in order to guarantee the rights of persons with disabilities and also the fulfillment of rights to physical and non-physical accessibility such as building facilities and infrastructure that must be adequate, or even because of employee resources, clerks, and judges in courts who need to understand related to various disability issues. This research is a juridical-normative legal research aimed at finding and formulating legal arguments, through an analysis of the subject matter. The technique of collecting legal materials is carried out by literature studies and field studies. The approach used is the statute approach, to examine the applicable legal rules related to disability, to see the provisions of the legislation and theoretical conceptions of disability with the empirical reality of the fulfillment of the rights of persons with disabilities at the Tanjung Karang High Court. The results show that based on the parameters of Government Regulation Number 39 of 2020 concerning Adequate Accommodation for Persons with Disabilities in the Judicial Process, that physical and non-physical accessibility at the Tanjung Karang High Court has been fulfilled properly, namely having special physical infrastructure and supporting tools. make it easier for persons with disabilities to access all public areas in court. Meanwhile, non-physical accessibility means that court officials have been provided with technical services regarding knowledge and ethics on how to serve persons with disabilities, and are now beginning to understand legal services for persons with disabilities.